Achieving Sustainable Development through Environment Accounting from the Global Perspective: Evidence from Bangladesh - Tapos Kumar (Asian Journal of Accounting Research, 2017)
The study visualizes the link between environment accounting & triple bottom line, quantitative environmental reporting & standard method, voluntary environmental disclosure & legal requirement, size of company & volume of environmental disclosure, material flow analysis & life cycle assessment to achieve sustainable development in Bangladeshi corporation. Therefore, the purpose of the study is to investigate the role of these factors to achieve sustainable development in Bangladeshi corporation. To investigate the role of these factors, ten factors that significantly contribute to achieve sustainable development were determined. A set of closed-minded questionnaire was developed on the basis of these factors to collect the data from employees & employers. Questionnaire was administered by using statistical tools such as matrix, cross tabulation & Paired Samples Tests as a data collection tool and analyses. Research finding shows that sustainability of corporation was associated with the performance of economic, social, and environment. Other factors like quantitative environmental reporting, standard method, voluntary environmental disclosure, legal requirement, size of the company, volume of environmental disclosure, material flow analysis & life cycle assessment were found that they worked as a complement to enhance the performance of economic, social, and environment to achieve sustainable development in Bangladeshi corporation.